Distal semimembranosus tendinopathy: A narrative review. Issue 8 (5th August 2021) - Sederberg, Mark; LaMarche, Laura; Skinner, Lee; Cushman, Daniel M.
Abstract: Distal semimembranosus tendinopathy is a relatively uncommon diagnosis that can be responsible for medial knee pain. The semimembranosus tendon inserts on the posteromedial knee and is surrounded by the semimembranosus bursa, with both the bursa and tendon potential sources of pain. Similar to other tendinopathies, semimembranosus tendinopathy often occurs with overuse of the musculotendinous unit and is commonly seen in runners. Diagnosis can be made clinically and may be substantiated with use of ultrasound or magnetic resonance imaging. Scant literature exists evaluating the efficacy of treatments for this condition. Consequently, best practice for treatment is inferred from other similar tendinopathies, clinical expertise, and smaller studies on semimembranosus tendinopathy. Extrapolating from other tendinopathies, rehabilitation should be the cornerstone of initial treatment, with focus on kinetic chain and gait abnormalities, hamstring strength and neuromuscular control, and progressive tendon loading. Recalcitrant cases with a coexisting bursopathy can be treated with an ultrasound‐guided bursal corticosteroid injection. Future studies may help delineate the optimal treatment regimen for this relatively uncommon diagnosis.